Crystalline thin films of silica: modelling, structure and energetics. (31st October 2018) - Wilson, Mark; Jenkins, Harry
Abstract: The static structural and energetic properties of thin crystalline films (̃two dimensional bilayers) of silica, SiO2, are modelled. Two potential models are considered in which the key interactions are described by purely harmonic terms and more complex electrostatic terms, respectively. The relative energetic stability of two potential crystalline forms, which represent alternative ways of tiling two dimensional space, is discussed. Coherent and incoherent distortions are introduced to the simulated crystals and their effects considered in terms of the ring structure formed by the Si atoms. The spatial relationship between distorted rings is analysed. An experimentally-observed single crystalline configuration is considered for comparison throughout.